Evaluation of an electronic antimicrobial time-out on antimicrobial utilization at a large health system. (17th May 2019) - Richardson, Steven R.; Neuner, Elizabeth A.; Athans, Vasilios; Srinivas, Pavithra; Wesolowski, Jill; Gordon, Steven M.; Fraser, Thomas G.
Abstract: We evaluated the impact of an electronic health record based 72-hour antimicrobial time-out (ATO) on antimicrobial utilization. We observed that 6 hours after the ATO, 21% of empiric antimicrobials were discontinued or de-escalated. There was a significant reduction in the duration of antimicrobial therapy but no impact on overall antimicrobial usage metrics.